The Impact of Aligning Kolb’s Experiential Learning Theory with a Comprehensive Teacher Education Model on Preservice Teachers’ Attitudes and Teaching Practice - Mechouat, Karima (European Scientific Journal, ESJ, 2024)
Since its inception, experiential learning has been a foundational tenant of teacher education. However, it is questionable to what extent authentic experiential learning practices are actually taking place. Based on Kolb’s Experiential Learning Theory Model, this paper presents an approach to addressing this issue. This exploratory manuscript further examines Kolb’s Experiential Learning Cycle (ELC) and considers its implications for Experiential Learning Theory (ELT) in teacher education. A description of the teacher education program in the CRMEF (Centre Régional des Métiers de l’Education et de la Formation) is provided, followed by results from a quantitative and qualitative survey triangulated with teacher trainees’ reflection journals to evaluate the training program in terms of the teacher trainees’ developing confidence and competence in teaching. This paper focuses on exploring the implementation of this approach for teacher education in the CRMEF. Results indicate that a large majority of the participants developed confidence in teaching through this approach, subsequently changing their perceptions and attitudes toward teaching English. Specific learning experiences that contributed to their confidence and competence include in-person, experiential, and hands-on approaches to learning relevant skills and knowledge, confirming the importance of using Kolb’s ELC as the foundation for teacher education programs. The study recommends that teacher educators should enhance their programs by providing pre-service teachers with instruction in authentic experiential learning pedagogy. Therefore, a comprehensive model for teacher education is proposed to demonstrate the role of experiential learning.